Two truths and a lie - O'Brien, Cory (Pantheon Books, 2025)
"In a mostly underwater near-future Los Angeles, aging combat-drone veteran Orr Vue now lives a simple and small life, trading snippets of what's become the most valuable currency: information. So when the cops show up at his door looking for data on a murder he's not even aware has happened, things get interesting for the first time in 25 years. At first, Orr is happy to exchange whatever he knows about the demise of InfoDrip's top exec to buy booze and pay rent on his memory storage, but that plan goes to hell when Orr's old boyfriend, Auggie Wolf, shows up as the number one suspect. Forced to stretch his atrophied spy skills and take his illegal horde of drones out of retirement alongside his busted knees, Orr finds himself in the crosshairs of the militarized police, a family of megarich corporate heirs, a clan of emancipated AIs, and a cult. Barely avoiding getting killed with every clue he collects, Orr realizes he's uncovered not just a murder, but a conspiracy that threatens Auggie's very existence. Ahh, the things we do for love... But in a world where memories can be bought and sold, how can you truly know who anyone is-or what you yourself are capable of? Fast paced, funny, and shockingly romantic, Two Truths and a Lie is Raymond Chandler reinvented for the 22nd century"--